2014
DOI: 10.3748/wjg.v20.i43.15943
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and hepatocellular carcinoma: A review and a point of view

Abstract: It is well recognized that one cause of chronic liver disease and hepatocellular carcinoma (HCC) is alcohol consumption. Research in Italy and the United States concludes that the most common cause of HCC (responsible for 32% to 45% of HCC) is alcohol. It has recently been shown that a significant relationship between alcohol intake, metabolic changes, and hepatitis virus infection does exist. Alcohol may be a factor in the development of HCC via direct (genotoxic) and indirect mechanisms (cirrhosis). There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 93 publications
1
82
0
1
Order By: Relevance
“…The drug-induced HCC model are generally used for simulating the hepatic tumor which is accumulated by long-time administration of different kinds of medications (Caviglia and Schwabe, 2015), while alcoholic beverages being included, it could also simulate the alcoholic liver cancer additionally (Thompson et al, 2015). For the substances used for inducing the HCC in this study, the DEN is a highly toxic chemical characterized by high risks for carcinogenicity, teratogenicity and genetic mutation, which is often used for induced HCC in mice (Zhao et al, 2015); the CCl 4 is also a common toxic chemical in the fields of chemical engineering and paint which can be a main component of rubber, detergent, pesticide and so on, except for the risks above, furthermore it has chronic toxicity on kidney and liver and could lead to hepatic steatosis, cirrhosis and enlargement of kidney (Cai et al, 2015); the spirit contains high content of alcohol, the 90% of which will be decomposed in liver, thereafter the ethyl alcohol and its metabolite acetaldehyde could directly damage the hepatocytes and probably lead to HCC (Testino et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The drug-induced HCC model are generally used for simulating the hepatic tumor which is accumulated by long-time administration of different kinds of medications (Caviglia and Schwabe, 2015), while alcoholic beverages being included, it could also simulate the alcoholic liver cancer additionally (Thompson et al, 2015). For the substances used for inducing the HCC in this study, the DEN is a highly toxic chemical characterized by high risks for carcinogenicity, teratogenicity and genetic mutation, which is often used for induced HCC in mice (Zhao et al, 2015); the CCl 4 is also a common toxic chemical in the fields of chemical engineering and paint which can be a main component of rubber, detergent, pesticide and so on, except for the risks above, furthermore it has chronic toxicity on kidney and liver and could lead to hepatic steatosis, cirrhosis and enlargement of kidney (Cai et al, 2015); the spirit contains high content of alcohol, the 90% of which will be decomposed in liver, thereafter the ethyl alcohol and its metabolite acetaldehyde could directly damage the hepatocytes and probably lead to HCC (Testino et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and epidemic studies have shown relationships between NASH and HCC development. Alcoholic liver disease (ALD) and ASH are the major causes of HCC in US [Morgan et al, 2004][Ramadori et al, 2017][Testino et al, 2014]. NASH has similar histological features with alcoholic hepatitis, such as overt lipid deposition and fat storage in the liver parenchymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to viral hepatitis, alcohol-induced liver damage is a major risk factor for developing HCC [20]. In a study investigating PIVKA-II levels in patients with benign alcoholic liver disease (ALD), 21% of cases had PIVKA-II levels above the cut-off value commonly used for the tumour marker [21].…”
Section: Performance Of Pivka-ii As a Hcc Tumour Markermentioning
confidence: 99%